Processing of Painful Pictures in Individuals With High and Low Rejection Sensitivity: Evidence From Event-Related Potentials. (September 2019) - Qinqin, Wu; Guangming, Ran; Qi, Zhang; Cao, Xiaojun
An increasing number of studies have investigated the relation between the processing of painful stimuli and rejection. Little was known, however, about the impact of the rejection sensitivity (RS) on the processing of painful pictures. This study addressed this issue using high temporal resolution event-related potential techniques. Thirty high RS (20 women and 10 men who scored in the top 20th percentile of the Rejection Sensitivity Questionnaire scores) and 30 low RS (20 women and 10 men who scored in the bottom 20th percentile) volunteers participated in the experiment. All volunteers performed a discrimination task of painful pictures in which they were asked to judge whether target pictures were painful or not. Behaviorally, participants exhibited shorter reaction times for painful than nonpainful pictures. For the P100 component, low RS participants showed stronger brain activities for painful than nonpainful pictures, suggesting vigilance toward painful pictures. High RS participants, however, exhibited no P100 amplitude differences between painful and nonpainful pictures, indicating an analgesia phenomenon. Furthermore, we found that there were larger amplitudes in the late late positive complex component for painful compared with nonpainful pictures, regardless of participants' RS. This suggested a person's further assessment for painful pictures. In short, our findings demonstrated that the level of RS influenced the pain processing at a very early stage of processing.